O estudo de nomes próprios de nipo-brasileiros de Terra Roxa - Nabão, Rosangela Martins (2006)
This study discusses theoretical results of the research project A Study of personal names of the Brazilians whom are Japanese descendents and live in Terra Roxa, Parana, Brazil . The purposes of this study is to try to understand the intercultural interaction among Japanese and their descendents in Brazil through the sociolinguistics information got with place research or ethnography and participant observation with traditional families group that have been living in the town, somebody since 1955, when the town was formed and to trace the history this people in this town as too. The research group is divided into the first generation - the immigrants that were born in Japan and began to live in Brazil, called isseis; the second generation - they are the first was born in Brazil, called nisseis; the third generation - they are grandsons and granddaughters of the Japanese immigrants, called sanseis. These participants are people were born since 1928 until 1999 and are involved in a sociocultural context. The personal names are the linguistic object of this study, showing how Brazilian and Japanese denominations belong to different onomastic systems: the oriental and the occidental, with morphological, syntactic and semantic different characteristics, but than they had evidenced that these etymons, first name and/or middle name and family one begin ethnic/cultural values and their traditions. The issues had evidenced the level of the adaptation and assimilation to the Brazilian culture and identity with more or less social representation of the Portuguese name and it has evidenced the pacific belonging cultural with creativeness. In 2008 will be completed 100 years what the first Japanese immigrants arrived in Brazil and it is not possible to say about this ethnic-descendents that they are invisible like participants of the historical, social and economical life in Brazil. In the other hand, the discussion had was showing than the various classified ethnic names as gaijn, several generations and adjectives that straight the Japan/Japanese, had indicated the stigmatization into the same country. This factor could take the identity crises, which is characteristic by the post-modernity. Then, beginnings of the knowledge of the cultural process Japanese person s personal name, in fact this search suggests that what is important above Brazil to need have recognized the interaction cultural and linguistic and respect to minorities groups and the education should have a culturally responsive pedagogy.